A novel probability density function applied to wind characterization in order to evaluate the wind power potential in Tungurahua, Ecuador's Andean region. Issue 6 (December 2018) - García del Valle, Javier; Mayorga, Alex; López, Germánico
In this investigation, the measured wind characteristics over the span of a year is reported for a location in the highlands of the Ecuadorian Andes. The first part of the article has been devoted to study the influence of the sampling rate on the annual power density by means of a number of techniques, namely the ensemble of means, aliasing, and Fourier low-pass filters. A byproduct of this analysis, once the wind frequency pattern was identified, has been the proposal of a new probability density function based on a daily Gaussian-weighted average of sinusoidal waveforms. The second part of the article thoroughly develops the proposed model along with a comparison with the measured data. The model proposed herein was found appropriate for describing poor class wind locations, as the one portrayed here, due to its ability of predict a zero wind probability.